Barriers and recommendations for parent–child conversations about pornography - Dawson, Kate; Gabhainn, Saoirse Nic; Friday, Ross; MacNeela, Pádraig (Frontiers in Sociology, 2024)
Parents consistently report being worried about the impact of online pornography on their adolescent and pre-adolescent children's development. Yet, most parents do not discuss pornography as part of parent-child conversations about sexuality. The current study sought to identify the barriers to parent-child conversations about pornography. This current article presents two studies. The first study employed one-to-one interviews to explore parents' (n = 14) beliefs about their role in their child's pornography education. The second study involved the quantitative assessment of Study 1 findings in a sample of parents of pre-adolescent and adolescent children (n = 408). Findings indicate that three overarching themes prevent parents from addressing pornography with their adolescent children, parents' practical ability to discuss pornography, their attitudes towards discussing pornography, and the perceived positive impact of addressing pornography with their adolescent children. Practical ability was most often reported as the greatest barrier to parents engaging in parent-child conversations about pornography. Most notably, parents reported hesitancy in discussing pornography because they did not know how to define pornography or how to address pornography in an age-appropriate way. Fathers were also significantly less likely to believe that talking about pornography was socially acceptable. We discuss the implications of these findings and present recommendations for developing a parents' pornography education resource.